(untitled) (Journal of the College of Basic Education, 2026)
The current research aimed to identify the reality of extracurricular activities among primary school students in mathematics from the perspective of teachers and supervisors, and to reveal whether their views on the reality of these activities differ based on gender, academic qualification, or years of experience. The researcher employed a descriptive methodology to understand the reality of implementing these activities, applying a questionnaire to a sample of (230) male and female teachers and supervisors. The results revealed no statistically significant differences in the reality of implementing activities attributed to the gender variable, while there were statistically significant differences regarding the academic qualification variable. As for the years of experience variable, results favored those with less than 10 years of experience. The researcher recommended that the Ministry of Education hold training courses on how to employ activities in their schools.